İmam Muhammed Şeybani'nin Hanefî Mezhebindeki Rolü ve Eserlerinin Neşrine Olan İhtiyaç - Şahi̇n, Sami (Dinî araştırmalar, 2006)
After giving brief information about the life and works of Imam Muhammad al-Shaibanit one of the prominent figures of the second century after hijra, we have focused on his mission in transferring the culture of hadith-fiqh to the following generations successfully. It is stated that he probably made the most important contribution for the views and thoughts belonging to the school of Hanafiya to live and reach our century. In addition, it is stressed that publishing his works today will be a gain for the scientific world. A list of manuscripts belonging to him is added to the study